A Critical Ethnography of Adult Learning In the Context of a Social Movement Group - Margaret L. Cain (Adult Education Research Conference, 1998)
This ethnography studied the learning among members of two groups in a toxic waste struggle with the EPA. The socio-political context, along with the members’ class, race and gender, significantly affected the members’ learning of technical and emancipatory knowledge.